Translation, Adaptation, and Validation of the Brazilian Version of the Dickman Impulsivity Inventory (Br-DII) - Gomes, Áurea K. V.; Diniz, Leandro F. M.; Lage, Guilherme M.; de Miranda, Débora M.; de Paula, Jonas J.; Costa, Danielle; Albuquerque, Maicon R. (Frontiers in Psychology, 2017)
Impulsivity has mainly been described as a negative or dysfunctional characteristic associated with several disorders. However, impulsivity is not only related to dysfunctional outcomes and may explain individual differences in optimal human functioning as well. The Dickman Impulsivity Inventory (DII) is a self-report instrument measuring both the dysfunctional and the functional aspects of impulsivity. In this study, we performed the translation and cultural adaptation of the DII to the Brazilian context and analysed its psychometric properties. Translation and cultural adaptation followed a rigorous process, which relied on an expert panel in the cross-cultural adaptation of psychological instruments. Data from 405 undergraduate students were obtained for the Brazilian version of the DII (Br-DII). The 23 items of the Br-DII was considered unsuitable according to model fit indices of the Confirmatory Factor Analysis (both for Oblique and Orthogonal models). Exploratory Factor Analysis showed an 18 items version of the Br-DII to be suitable (CFI = .92; TLI = .90, and RMSEA = .057). The DII’s 18 items version also showed adequate Cronbach's Alpha, intraclass correlation coefficient, and convergent and discriminant validity with the BIS-11. Therefore, the Br-DII demonstrated reliability and validity in the measurement of functional and dysfunctional impulsivity.